Desarrollo de un sistema de catálogo virtual con generador de código QR para el Local Comercial Chávez. - Iza Iza, Alex Ismael (2023)
The purpose of this technological proposal is to design a virtual catalog for the "Chávez" store, which sells tires, rims and accessories for automobiles, in order to provide the store with a guide to technify its advertising to its customers and to easily face the threats that arise in the market. The approach used was qualitative-quantitative, under the modalities of documentary - bibliographic, field and descriptive research. The survey of requirements was obtained through an interview focused on the Manager with the objective of knowing the processes and important documentation that she develops. On the other hand, we chose to adapt the Scrum methodology by selecting the roles of the work team for the implementation of the computer system, which is why we took into account a Scrum master, development, product owner, in the same way we used the chart.js library, the MySqL database, the controller view model pattern, which allowed the development of a functional software with graphs equipped with filters for the execution of activities generated by the Commercial Premises.